Antiperiodic Boundary Value Problems for Second-Order Impulsive Ordinary Differential Equations. (15th January 2009) - Bai, Chuanzhi
Abstract : We consider a second-order ordinary differential equation with antiperiodic boundary conditions and impulses. By using Schaefer's fixed-point theorem, some existence results are obtained.